Connecting Families? 2018
DOI: 10.1332/policypress/9781447339946.003.0009
|View full text |Cite
|
Sign up to set email alerts
|

Use of communication technology to maintain intergenerational contact: toward an understanding of ‘digital solidarity’

Abstract: This chapter examines the use of communication technology (emailing and texting) for the maintenance of digital solidarity. It first considers the role of digital solidarity in the study of intergenerational solidarity, and more specifically how digital solidarity adds a new dimension to the concepts of associational solidarity and functional solidarity. It then explores the use of emailing and texting by older mothers to maintain contact with their adult children using data from two US sources and from differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…The use of text and other digital forms of communication may serve to enhance what Peng et al (, p. 159) refer to as “digital solidarity.” Digital solidarity builds on the premise of associational solidarity by fostering relationship strength through contact (Bengtson & Oyama, ; Fingerman et al, ; Silverstein & Giarrusso, ). Indeed, new technologies have facilitated contact between social partners in general (Cotten, McCullough, & Adams, ), and the same may be true of adults and parents.…”
Section: Technologies and Contact Between Adults And Their Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of text and other digital forms of communication may serve to enhance what Peng et al (, p. 159) refer to as “digital solidarity.” Digital solidarity builds on the premise of associational solidarity by fostering relationship strength through contact (Bengtson & Oyama, ; Fingerman et al, ; Silverstein & Giarrusso, ). Indeed, new technologies have facilitated contact between social partners in general (Cotten, McCullough, & Adams, ), and the same may be true of adults and parents.…”
Section: Technologies and Contact Between Adults And Their Parentsmentioning
confidence: 99%
“…Likewise, from 2008 to 2011, slightly less than one third (31%) of older mothers had either texted or emailed a grown child in the past year. Newer data obtained from better‐educated mothers in 2016 found that 95% of mothers reported instant messaging or emailing a grown child (Peng et al, ).…”
Section: Technologies and Contact Between Adults And Their Parentsmentioning
confidence: 99%
“…Second, the concept of associational solidarity has recently been extended to include ‘digital solidarity’ to consider the role of technology in maintaining contact between the generations (Peng et al, 2018). Digital communication between generations represents a new domain in gerontological research but one that is receiving increased attention.…”
Section: Theoretical Perspectives On Multigenerational Family Relatiomentioning
confidence: 99%
“…During the pandemic, families are encouraged to utilize technology (e.g., FaceTime or Zoom) (Glazer, 2020). As noted above, scholars have developed the term ‘digital solidarity’ to recognize the use of such communication technology to maintain intergenerational support (Peng et al, 2018). Such digital communication may be particularly beneficial to combat loneliness among older adults who live alone or in assisted and independent living communities (Cotten et al, 2013; Czaja, 2017; Czaja et al, 2018) and cannot receive family members' visits.…”
Section: Multigenerational Social Support Exchanges and The Covid‐19 mentioning
confidence: 99%
See 1 more Smart Citation